Failure of empire : Valens and the Roman state in the fourth century A.D - Lenski, Noel Emmanuel (University of California Press, 2003)
This is a comprehensive biography of the Roman emperor Valens and his troubled reign (AD 364-78). Valens will always be remembered for his spectacular defeat and death at the hands of the Goths in the Battle of Adrianople. The text incorporates material from archaeology to Gothic and Armenian sources